PENERAPAN MULTIMEDIA INTERAKTIF BERBASIS INKUIRI TERBIMBING DALAM PEMBELAJARAN IPS SISWA KELAS IV SEKOLAH DASAR - Priyanto, Wawan (Mimbar Sekolah Dasar, 2016)
This research is describing a prototype of multimedia interactive based on guiding inquiry. Research subject was obtained at fourth grade of SDN Pedurungan Kidul 01. Design and display this media be adapted by the student’s character. Teaching media products are approved by one who validated before used. One who validated was two lecturers and a teacher of fourth grade. The practicality of this research obtained at observation data from the teacher’s ability to manage the class and the students’ responses to multimedia interactive based on guiding inquiry. Based on the data could be concluded that the development of multimedia interactive based on guiding inquiry is valid, practical and effective in learning IPS at fourth grade of elementary school. This media could help the students’comprehension in formulate the problems, collect the data, analyzing and conclusion the problems. Keywords: interactive multimedia, guiding inquiry, students in fourth grade of elementary school.